2014
DOI: 10.1007/s00018-014-1661-9
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally abundant exceptions: comprehensive characterization of intrinsic disorder in all domains of life

Abstract: consensus-based disorder predictions, and for the first time comprehensively characterized intrinsic disorder at proteomic and protein levels from all significant perspectives, including abundance, cellular localization, functional roles, evolution, and impact on structural coverage. We show that intrinsic disorder is more abundant and has a unique profile in eukaryotes. We map disorder into archaea, bacterial and eukaryotic cells, and demonstrate that it is preferentially located in some cellular compartments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
270
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 342 publications
(291 citation statements)
references
References 55 publications
(123 reference statements)
21
270
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Several recent studies (mostly of computational nature) revealed that IDPs are very common in various proteomes, with the proteome content of IDPs being typically an indicator of both evolution and adaptation to the environment. 1,18,[42][43][44][45][46] In fact, the percentage of IDPs in proteomes is increasing from bacteria and archaebacteria, to fungi, and to eukaryotic organisms, thereby reflecting the evolutionary importance of intrinsic disorder. 42,[44][45][46] On the other hand, the role of disorder in adaptation to the environment can be illustrated by the fact that the salt, pH, and/or temperature-tolerant bacteria and Achaea typically contain more IDPs than their mesophilic and salt/pH-sensitive counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Several recent studies (mostly of computational nature) revealed that IDPs are very common in various proteomes, with the proteome content of IDPs being typically an indicator of both evolution and adaptation to the environment. 1,18,[42][43][44][45][46] In fact, the percentage of IDPs in proteomes is increasing from bacteria and archaebacteria, to fungi, and to eukaryotic organisms, thereby reflecting the evolutionary importance of intrinsic disorder. 42,[44][45][46] On the other hand, the role of disorder in adaptation to the environment can be illustrated by the fact that the salt, pH, and/or temperature-tolerant bacteria and Achaea typically contain more IDPs than their mesophilic and salt/pH-sensitive counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…1,18,[42][43][44][45][46] In fact, the percentage of IDPs in proteomes is increasing from bacteria and archaebacteria, to fungi, and to eukaryotic organisms, thereby reflecting the evolutionary importance of intrinsic disorder. 42,[44][45][46] On the other hand, the role of disorder in adaptation to the environment can be illustrated by the fact that the salt, pH, and/or temperature-tolerant bacteria and Achaea typically contain more IDPs than their mesophilic and salt/pH-sensitive counterparts. 31,47 Many aspects related to the structure, conformational behavior and functionality of IDPs look rather strange from the viewpoint of "traditional" ordered proteins.…”
Section: Introductionmentioning
confidence: 99%
“…1 In fact, computational studies suggest that all proteomes of organisms in all kingdoms of life and all viral proteomes analyzed so far have considerable quantities of IDPs and IDPRs. [2][3][4][5][6][7][8] It has also been shown that the length and frequency of disordered regions are both greater in organisms of higher complexity, with at least one third of all eukaryotic proteins containing long IDPRs 4 and more than one tenth of these proteins being fully disordered. 9 Furthermore, considerably less than 30% of the crystal structures in the Protein Data Bank (PDB) are known to have no disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The structure-less intrinsically disordered proteins (IDPs) and intrinsically disordered protein regions (IDPRs) are commonly found in various proteomes [1][2][3][4][5][6], where they functionally complement ordered proteins and domains, typically playing important roles in cell signaling, as well as regulating and controlling various crucial biological processes [7][8][9][10][11][12][13][14][15][16][17][18][19]. IDPs/IDPRs are very promiscuous binders that are constantly involved in various interactions with diverse partners [20,21] and are known to play key roles in protein-protein interaction networks [13,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%